Factors Hindering ICT Implementation in Indian Insurance Industry: An Empirical Study - Odoyo, Fredrick S.; Nyangosi, Richard; Gupta, H. P. (Indian Journal of Finance, 2009)
Rapid advances in information and communication technology (ICT) are changing the way business is done everywhere. The Insurance business is being changed by ICT too. Exactly where the changes is leading is unforeseeable, by change is inevitable and intelligent participants in insurance business want to take advantage of it.This research paper will focus on ICT from corporate perspective, implementation and factors hindering the corporate sector from embracing ICT in the insurance industry. The data for this study was obtained from the primary survey both from private and public insurance companies. To analyze the data, different techniques including, cross-tabulation, weighted average score analysis, Chi-square and ANOVA were used.The results of the study indicate that the private sector has so much implemented ICT infrastructure, for instance, hardware soft ware and networking, more than public insurance firms. Also it was revealed that scarcity of skilled staff, conventional attitude, complicated ICT technologies and product complexities were some of the important factors hindering the spread of ICT in Indian insurance industry.